Eksistensi Pesantren Alam Indonesia sebagai Lembaga Dakwah di Desa Harapan Kabupaten Barru - Wahyudi AR, Nirwan (KOMUNIDA : Media Komunikasi dan Dakwah, 2023)
This article reveals the existence of the Indonesian Natural Islamic Boarding School as a da'wah institution and its contribution to the development of da'wah in Harapan Village, Barru Regency. Qualitative research methods with a phenomenological paradigm are used by the author. The background to the existence of the Indonesian Nature Islamic Boarding School is expressed through the because-motive and the in-order-to-motive. The contribution of the Indonesian Nature Islamic Boarding School to the development of da'wah in Harapan Village, Barru Regency includes the fields of irsyad, tabligh, administration, and most significantly in the field of tatwhir. Several supporting and inhibiting factors were identified related to the development of da'wah by the Indonesian Nature Islamic Boarding School in Harapan Village, Barru Regency. Supporting factors include a strategic location, located in the midpoint zone of Indonesia; Managers and coaches with diverse knowledge and experience backgrounds; and The existence of varied and productive business units. However, there are also inhibiting factors which include: The orientation of Islamic boarding schools which still tends to focus on internal development or students; The number of students from the local village is still less than 50%; and Lack of concrete cooperation between pesantren administrators and the local village/hamlet government.